Spatial Analysis of Landscape Change in the Puncak Bogor Cianjur Tourism Area 2013-2023 - Prasetya, Ferdian Adhy; Purwaningsih, Yuli; Nagara, Rakyan Paksi; Raditia, Mohammad; Junaid, Muhammad; Kusratmoko, Eko (Universitas Muhammadiyah Purwokerto, 2025)
This research analyzes the dynamics of land cover change in the Puncak Area over the last 10-year period (2013-2023). Using the Random Forest Classification method on Landsat 8 and 9 image data, this study evaluates the contribution of tourism to the economy of the Puncak Region and reveals facts related to land use change. The Puncak area, known as a mountain tourism destination in West Java, is experiencing rapid economic growth, but tourism activities and infrastructure development have the potential to negatively impact local ecosystems. The research used BIG administrative data, Landsat imagery, and landform systems for analysis. Through Google Earth Engine (GEE), data processing was performed, including cloud masking, mosaic, clip, and pan-sharpening. The Random Forest classification method was used to determine land cover in 2013 and 2023 with kappa accuracy tests reaching 85.81% and 88.42% respectively. The results show an increase in built-up land area of 4,632.68 hectares with a decrease in agricultural and forest land. Obstacles in the interpretation of low-resolution Landsat imagery became one of the challenges in this study. The Urban Expansion Intensity Index (UEII) calculation results show a moderate increase in built-up land area over the past 10 years. The phenomenon of urbanization and the drive of economy and tourism are the main factors of land change from vegetation cover to built-up land. This study provides important insights for the regulation and monitoring of the Puncak Area to maintain a balance between economic growth and environmental sustainability.